(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the impact of training on enhancing employee efficiency and improving organizational performance at Nault Central Hospital. To achieve this objective, the study employed a descriptive-analytical approach, given its suitability for the subject matter. The study population comprised all hospital staff and personnel, while a representative sample was selected to include administrative, medical, and paramedical staff from key departments (Pharmacy, Anesthesia, Intensive Care, Pediatrics, and Obstetrics). A questionnaire served as the primary tool for collecting data and preliminary information; the data were subsequently processed, and the necessary statistical analysis was conducted to test and verify the hypotheses, The study reached several key findings, most notably; Training programs have a statistically significant positive impact on enhancing employee competence and developing practical skills within the hospital There is a strong positive correlation between the level of employee competence gained through training and improvements in overall organizational performance and the quality of healthcare services provided, The results revealed relative variations in training needs across different departments (such as anesthesia and intensive care compared to other departments) Based on these findings, the study recommended continuing and intensifying specialized training programs at Nault Central Hospital and linking training pathways with career progression, while focusing on assessing the actual needs of each department to ensure the highest levels of performance competence